Analisis Kepuasan Mahasiswa STMIK Widuri terhadap Pelayanan Bagian Keuangan Menggunakan Metode Service Quality (SERVQUAL) - Serlianti Waruwu; Nur Nawaningtyas (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to analyze student satisfaction with the administrative services of the Finance Department at STMIK Widuri, utilizing the SERVQUAL method. Effective administrative services are crucial for supporting the quality of higher education and the institution's reputation. Through a questionnaire designed based on the five dimensions of SERVQUAL reliability, responsiveness, assurance, empathy, and tangible evidence data were collected from active students. The analysis results are expected to identify areas for improvement in financial services and provide concrete recommendations to enhance service quality. This research aims to offer insights for decision-makers at STMIK Widuri to improve the efficiency and effectiveness of financial services while meeting student needs. Additionally, the findings are anticipated to enhance STMIK Widuri's image as a responsive institution towards student requirements. The study also emphasizes the importance of understanding student expectations in efforts to improve service quality in higher education.